Patients' Perceptions of Compliance with Tuberculosis Medication in Lamongan - Octavia, Devi Ristian; Utami, Primanitha Ria (Universitas Islam Lamongan, 2020)
Treatment non-adherence in tuberculosis (TB) patients is a challenge in TB treatment. This research was an observational analysis study with a cross-sectional design. The population of this study were all tuberculosis patients at Karanggeneng Community Health Center, Lamongan from January to September 2018 who were still undergoing treatment process. Total sampling technique was utilized which obtained 40 patients. The data were collected through a closed questionnaire sheet of the method applied by the MMAS (Morisky Medication Adherence Scale). Then, the data were analyzed by editing, coding, scoring and tabulating. The results showed that 92% of patients adhered to Tuberculosis treatment and their influential perceptions included patients’ belief, family support, and motivation from health personnel. Treatment supporter is very influential on the success of Tuberculosis therapy.